Requirements for a Pattern Language for Event-driven Business Activity Monitoring - Raffelsieper, Thomas; Becker, Jörg; Matzner, Martin; Janiesch, Christian (Multikonferenz der Wirtschaftsinformatik (MKWI 2012), 2012)
To measure and evaluate the productivity of service processes in near real-time, the fusion of Complex Event Processing (CEP) and Business Activity Monitoring (BAM) for Business Process Management (BPM) has been proposed under umbrella terms such as event-driven BAM or event-driven BPM. However, evaluations of the resulting architectures have shown that there is a need for structured design methods which allow for the consistent engineering and management of the respective models. Since we observed repetitive patterns in BAM queries for service monitoring, we have started the engineering of a pattern language to increase consistency and generally ease the design process. Based on an evaluation of related work, we present more than two dozen requirements of general nature as well as requirements for sourcing, calculation, and evaluation definitions and discuss these.